Penyuluhan Pencegahan Pernikahan Dini Pada Remaja Desa Balane Sigi: remaja, penyuluhan, pernikahan dini - Moh.Rizky; Nuriyana Abd.Hakim; Maria Tambunan (CV. Multi Kreasi Media, 2022)
Indonesia is ranked second in ASSEAN and ranked 8th in the world in cases of early marriage. According to 2017 BPSN data, Central Sulawesi Province ranks 11th in early marriage. According to the 2014 BKKBN data in Prabantari (2016), showing that early marriages carried out by women aged 15-19 years in Indonesia reached 46%. According to Central Sulawesi BPS data (2017), Sigi Regency is ranked 5th, where it is known that Balane Village belongs to Sigi Regency. Marawola sub-district was ranked first in cases of female early marriage with a percentage of 18.9% in Sigi District, especially in South Tinggede Village. Based on the results of initial observations, cases of early marriage in Balane Village, Sigi Regency are increasing, this is based on data from the village office and data from the results of the study of many teenagers who marry at a young age, 5 heads of families who are still 20 years old, for mothers aged less from 20 years as many as 10 people and based on the results of interviews conducted during resident observations during field practice, the number of divorces in early married couples occurred before the completion of reporting in the civil registry. Objective: The purpose of Community Service is to provide awareness and information about the importance of reducing the number of early marriages in order to improve the quality of human resources. Method: the method used is lecture and discussion method using powerpoint media. The result, based on the results of observations, regional mapping and interviews, shows that there is an increase in early marriage which causes health problems for mothers and children, so it is necessary to provide health education. Results: The results obtained during the observation that the residents of Balane Village have a family head with as many as 5 families and the number of divorces due to early marriage before the registration of civil registration is carried out. It is hoped that after the counseling will increase public knowledge and can prevent early marriage.